ANALISIS TEORI HAK MILIK DAN UTILITARIANISME TERHADAP PRAKTIK DIRECT LICENSING DALAM INDUSTRI MUSIK DI INDONESIA - Nanda Octavian Permata Kusuma; Hwian Christianto (The Juris, 2026)
The governance of music royalties in Indonesia has reached a critical juncture due to ongoing tensions among songwriters, performers, and Collective Management Organizations (CMOs/LMKN). This study aims to analyze the legal standing of direct licensing practices undertaken by songwriters who remain affiliated with Collective Management Organizations under Law Number 28 of 2014 concerning Copyright (Copyright Law), and to examine the legality of such independent royalty collection through the perspectives of John Locke’s Property Rights Theory and Jeremy Bentham’s Utilitarian Theory. Employing a normative legal research method through statutory, conceptual, and comparative approaches, this study finds that the legal position of independent direct licensing by songwriters bound to CMOs is contractually weak. Nevertheless, recent jurisprudential developments through Supreme Court Decision Number 825 K/Pdt.Sus-HKI/2025 and Constitutional Court Decision Number 28/PUU-XXIII/2025 have reaffirmed the reallocation of responsibility for the payment of royalties arising from commercial performances from performers (singers) to event organizers (promoters), while also requiring the application of restorative justice prior to the imposition of criminal sanctions. From a theoretical perspective, direct licensing is justified under Locke’s Property Rights Theory as a form of self-help remedy aimed at restoring individual rights in response to the malfunctioning of the collective management system. However, it is rejected under Bentham’s Utilitarian Theory in the long term because it undermines market efficiency and significantly increases transaction costs. This study recommends the adoption of a hybrid licensing system and the implementation of a transparent and digitally integrated SILM platform.